Who's my little monkey? Effects of infant‐directed speech on visual retention in infant rhesus macaques. Issue 2 (29th December 2016) - Slonecker, Emily M.; Simpson, Elizabeth A.; Suomi, Stephen J.; Paukner, Annika
Abstract: Both human and nonhuman primate adults use infant‐directed facial and vocal expressions across many contexts when interacting with infants (e.g., feeding, playing). This infant‐oriented style of communication, known as infant‐directed speech (IDS), seems to benefit human infants in numerous ways, including facilitating language acquisition. Given the variety of contexts in which adults use IDS, we hypothesized that IDS supports learning beyond the linguistic domain and that these benefits may extend to nonhuman primates. We exposed 2.5‐month‐old rhesus macaque infants ( N = 15) to IDS, adult‐directed speech (ADS), and a non‐social control (CTR) during a video presentation of unrelated stimuli. After a 5‐ or 60‐minute delay, infants were shown the familiar video side‐by‐side with a novel video. Infants exhibited a novelty preference after the 5‐minute delay, but not after the 60‐minute delay, in the ADS and CTR conditions, and a novelty preference in the IDS condition only after the 60‐minute delay. These results are the first to suggest that exposure to IDS affects infants' long‐term memory, even in non‐linguistic animals. Abstract : Using a visual‐paired comparison test, we found that exposure to infant‐directed speech (IDS) during encoding inhibited visual discrimination 5 minutes after exposure but increased discrimination 60 minutes after exposure in infant rhesus macaques. These results are the first to suggest that exposure to IDS affects infants' long‐term memory, even in non‐linguistic animals.